INVESTIGATION OF PERMANENT TEETH IMMATURE ENAMEL CHANGES INFLUENCED BY REMINERALIZING GEL WHICH CONTAINS CALCIUM, PHOSPHORUS AND MAGNESIUM - G. Sorochenko (Bogomolets National Medical University, 2015)
Conclusions. It was found that enamel of the permanent teeth germs is not mineralized and therefore has insufficient level of caries resistance. Without the use of additional means of prevention level of caries resistance of the permanent teeth germs enamel remains insufficient even after 12 months of the experiment. The chemical composition of superficial enamel layer of permanent teeth germs changes under the influence of remineralizing gel which contains calcium, phosphorus and magnesium. Achieving the optimal level of mineralization under the influence of remineralizing gel containing calcium, phosphorus and magnesium occurs in the experiment after 12 months of use.